Persepsi Guru dan Siswa Jurusan Akuntansi di SMKN 1 Negara Tentang Penghapusan Ujian Nasional - Yasa, I Gede Palguna; Indrayani, Luh (Jurnal Pendidikan Ekonomi Undiksha, 2021)
This study aimed at determining the perceptions of teachers and students of the Accounting Department at SMKN 1 Negara on the elimination of the national exam. The research design used was a descriptive study which describes teachers’ and students’ perception toward the elimination of national examination. This study involved all accounting teachers and students of SMK Negeri 1 Negara as a population. Meanwhile, the samples of this study were 10 accounting teachers and 198 accounting students. These samples were determined by using the Solvin formula. In collecting the data, the instrument used was a questionnaire. The obtained data were analyzed through descriptive analysis. The results of this study show that teachers’ perception from the internal factor dimension obtained a score of 398 which is included in the agreed category. Further, the external factor dimension obtains a score of 439 which is also included in the agreed category. Moreover, students' perceptions of the internal factor dimension obtained a score of 7,814 which is included in the agreed category. Furthermore, the external factor dimension obtains a score of 8,464 which is included in the agreed category. From the results, it can be concluded that the teachers and students of the Accounting Department at SMKN 1 Negara agree with the elimination of the national examination.